Body shopping: Challenging convention in the donation and use of bodily materials through art practice. Issue 2 (1st October 2020) - Mackenzie, Louise; Turkmendag, Ilke; Burr-Raty, Isabel; Hunter, WhiteFeather; Jarvis, Charlotte; Simun, Miriam; Tapio, Hege; Zaretsky, Adam
The historical context of body and tissue donation is deeply problematic, with patriarchal and colonial narratives. The contemporary context of molecular and genetic biology further complicates issues of bodily donation through narratives of abstraction and extraction. As practitioners working outside the conventional boundaries of scientific study learn the tools and techniques to extract and use bodily materials, they are also learning and challenging the procedures and processes. This article approaches questions of bodily donation through the edited transcript of a conversation between artists who regularly use body fluids and cellular bodily materials in their practice, moderated by Louise Mackenzie and Ilke Turkmendag as part of the Taboo‐Transgression‐Transcendence in Art & Science Conference held online with the support of the University of Applied Arts, Vienna, 2020. The panel challenged the ethical and conceptual assumptions made in biotechnological research and reconsidered where the boundaries of the body lie, what 'authority' research carries and what choices researchers make when using the bodies of others. The transcribed conversation addresses taboos of the female body, specifically menstruation, the commodification of tissue from female human bodies, human milk politics and questions biopolitical treatment of the female body. The full, unedited panel conversation, including questions from the audience, and an accompanying video of edited interviews with panellists, is available online at https://www.loumackenzie.com/offering-the-body .